The Islamic Bank of Malaysia: its loan operations as compared with commercial banks and finance companies - Awang, Adibah (1984)
The paper attempts to make a comparison between the present loan operations of commercial banks and finance companies with that of the Islamic bank. This study was undertaken because of the current interest in the application of Islamic principles in the present banking system and also due to the recent establishment of Malaysia's first Islamic Bank.